Reliability, usefulness, and validity of field-based vertical jump measuring devices - Comyns, T. M.; Murphy, J.; O'Leary, D. (The Journal of Strength and Conditioning Research, 2023)
The purpose of this study was to examine the test-retest reliability, usefulness, and validity of field-based devices, in determining jump height (JH) during a countermovement jump (CMJ). Twenty-one male (22.8 ± 2.4 years; 1.82 ± 0.07 m; 86.0 ± 10.4 kg) and 7 female field sport athletes (20.5 ± 1.5 years; 1.65 ± 0.06 m; 65.4 ± 7.2 kg) performed 3 CMJs with data simultaneously recorded using a force plate (criterion measure), Optojump, Output Capture, and Push-Band 2.0. Reliability was determined by intraclass correlation (ICC) and coefficient of variation (CV) analyses. Usefulness was assessed by comparing typical error (TE) with the smallest worthwhile change (SWC), and the validity analyses involved repeated measures analysis of variance with post hoc analysis, Pearson correlation coefficient (r), coefficient of determination, and Bland-Altman 95% limits of agreement analyses. All 3 field-based devices were deemed reliable in assessing CMJ height as the respective ICCs = 0.80 and the CV = 10%. Only the Optojump and Output Capture devices were rated as "good" at detecting the SWC in performance (Optojump SWC: 1.44 > TE: 1.04; Output Capture SWC: 1.47 > TE: 1.05). The Output Capture device demonstrated acceptable validity for CMJ height assessment, whereas the Push-Band 2.0 showed systematic bias when compared with the criterion force plate data. Systematic difference was also evident for the Optojump potentially due to the optical switching-cell position on the Optojump. Although all 3 devices showed excellent reliability, the Optojump and Output Capture devices offer practitioners a cost effective, reliable, and valid method of assessing the smallest worthwhile change in CMJ performance in an applied setting.